let L, E be Z_Module; :: thesis: for I being Subset of L
for J being Subset of E st ModuleStr(# the carrier of L, the addF of L, the ZeroF of L, the lmult of L #) = ModuleStr(# the carrier of E, the addF of E, the ZeroF of E, the lmult of E #) & I = J holds
Lin I = Lin J

let I be Subset of L; :: thesis: for J being Subset of E st ModuleStr(# the carrier of L, the addF of L, the ZeroF of L, the lmult of L #) = ModuleStr(# the carrier of E, the addF of E, the ZeroF of E, the lmult of E #) & I = J holds
Lin I = Lin J

let J be Subset of E; :: thesis: ( ModuleStr(# the carrier of L, the addF of L, the ZeroF of L, the lmult of L #) = ModuleStr(# the carrier of E, the addF of E, the ZeroF of E, the lmult of E #) & I = J implies Lin I = Lin J )
assume that
A1: ModuleStr(# the carrier of L, the addF of L, the ZeroF of L, the lmult of L #) = ModuleStr(# the carrier of E, the addF of E, the ZeroF of E, the lmult of E #) and
A2: I = J ; :: thesis: Lin I = Lin J
L is Submodule of E by ;
hence Lin I = Lin J by ; :: thesis: verum